Pre-treatments to reduce metabolism in adult green-lipped mussel, Perna canaliculus, in preparation for live transportation - M. C. F. Cheng; L. N. Zamora; N. L. C. Ragg; A. J. R. Hickey; B. J. Dunphy (Aquaculture International, 2024)
Improved sustainability of aquaculture can be achieved by reducing product wastage post-harvest. Aquaculture of the green-lipped mussel, Perna canaliculus , is an important industry for New Zealand, which increasingly exports to live markets. Live transport can keep mussels fresh, but mussels could also be susceptible to handling stresses. To remedy this, pre-treatments that make mussels metabolically depressed, and thus potentially less sensitive to external stressors, were explored. As indicators of depressed metabolism, heart rate (HR), inferred cardiac output (PCO), and relative gaping magnitude (RGM) were simultaneously monitored in mussels experiencing different temperatures, dissolved oxygen levels and anaesthetic (MgCl 2 ) concentrations to compare their efficacy in inducing suppressed metabolism of adult P. canaliculus . We found complex interactions between HR, PCO, and RGM in response to these conditions; however, overall, these response variables were significantly correlated. Mussels showed depressed HR and PCO by up to 100% at 4 °C within 2 h, with correspondingly decreased RGM of up to 48%. Similarly, mussels immersed in 40 g L −1 MgCl 2 suppressed HR by up to 97%, accompanied by up to 76% decrease in PCO, and a slight increase in RGM (11%) after 2 h. While responses were variable, low DO levels suppressed HR by up to 50%, yet PCO and RGM increased two- and threefold relative to control groups. The results of the present study indicated that 4 °C and 40 g MgCl 2 L −1 were more effective conditions as pre-treatments than low dissolved oxygen lower the metabolism of P. canaliculus before live transport.